Molecular sensitised probe for amino acid recognition within peptide sequences - Wu, Xu; Borca, Bogdana; Sen, Suman; Koslowski, Sebastian; Abb, Sabine; Rosenblatt, Daniel Pablo; Gallardo, Aurelio; Mendieta-Moreno, Jesús I; Nachtigall, Matyas; Jelinek, Pavel; Rauschenbach, Stephan; Kern, Klaus; et al. (Nature communications, 2023)
The combination of low-temperature scanning tunnelling microscopy with a mass-selective electro-spray ion-beam deposition established the investigation of large biomolecules at nanometer and sub-nanometer scale. Due to complex architecture and conformational freedom, however, the chemical identification of building blocks of these biopolymers often relies on the presence of markers, extensive simulations, or is not possible at all. Here, we present a molecular probe-sensitisation approach addressing the identification of a specific amino acid within different peptides. A selective intermolecular interaction between the sensitiser attached at the tip-apex and the target amino acid on the surface induces an enhanced tunnelling conductance of one specific spectral feature, which can be mapped in spectroscopic imaging. Density functional theory calculations suggest a mechanism that relies on conformational changes of the sensitiser that are accompanied by local charge redistributions in the tunnelling junction, which, in turn, lower the tunnelling barrier at that specific part of the peptide.
Keywords: Peptides; peptidy; Microscopy, Scanning Tunneling; sekvence aminokyselin; Molecular Probes; Amino Acids; rastrovací tunelová mikroskopie; Amino Acid Sequence; aminokyseliny; molekulární sondy